FOREST-BASED INDUSTRY IN PARANÁ: BIOENERGY CLUSTERING AND GENERATION - Hersen, Amarildo; Timofeiczyk Junior, Romano; Silva, Dimas Agostinho; Da Silva, João Carlos Garzel Leodoro; Ferrera de Lima, Jandir (Floresta, 2019)
The territorial proximity of economic and social agents operating in an activity can result in agglomeration economies related, among other things, to more ease of access to knowledge, training of skilled labor, raw materials and equipment. The problem of the present research is to understand if there is a concentration of timber products from forest-based industries in the state of Paraná. The goal of this study was to identify the regions of Paraná that make up the main cluster of the forest-based industry and analyze it from the perspective of the installed capacity for electric power generation from forest biomass. The research methodology adopted was multivariate analysis, by interdependence technique, through cluster analysis. This technique makes it possible to classify the Paraná regions into groups so that each region resembles the others in the cluster but differs from the other clusters based on a set of characteristics – number of forest-based industries, number of jobs in the forest-based industry, Tax Value Added and planted forest area. The results suggest the existence of two clusters. In the main cluster, all the Geographic Microregions exploit forest biomass for electric power generation, and account for 99.4% of the total capacity of Paraná in terms of electricity generation from forest biomass, with potential for expanding the installed capacity.